"Have We Done Enough?" A Cross-condition Exploration of the Experiences of Parents Caring for A Child with an Appearance-affecting Condition or Injury. (18th August 2021) - Thornton, Maia; Harcourt, Diana; Deave, Toity; Kiff, James; Williamson, Heidi
ABSTRACT: Children and young people (CYP) with appearance-affecting conditions/injuries report common pervasive psychosocial difficulties, regardless of cause, nature or extent of their visible differences. Parents or carers can also experience psychosocial difficulties and challenges specific to having CYP with a visible difference. Current literature is confined to exploring condition-specific concerns of parents, typically in more prevalent appearance-affecting conditions/injuries, whilst the experiences of parents of CYP with other visible differences are unknown. Thirty-one interviews (parents n = 20, health and support professionals n = 11) and 4 parent focus groups (n = 25) were conducted. Three overarching themes were constructed: "Appearance does(n't) matter" describes the impact of having a child with a socially undesirable appearance; "Being 'battle' ready" reflects parents' desire to arm their child with resources to manage challenges, whilst "Walking the tightrope" reflects parents' lack of clarity about how best to approach this. Findings highlight shared and common cross-condition psychosocial difficulties among parents and carers.